Cultivating resilience in wheat: mitigating arsenic toxicity with seaweed extract and Azospirillum brasilense - Zaheer, Muhammad Saqlain; Aijaz, Nazish; Hameed, Akhtar; Buttar, Noman Ali; Rehman, Shamsur; Riaz, Muhammad Waheed; Ahmad, Ajaz; Manzoor, Muhammad Aamir; Asaduzzaman, Muhammad (Frontiers in Microbiology, 2024)
Arsenic (As) toxicity is a serious hazard to agricultural land due to growing industrialization, which has a negative effect on wheat crop yield. Using seaweed extract and Azospirillum brasilense has become known as an appropriate approach for yield improvement under stress conditions in order to address this problem. The combined application of A. brasilense and seaweed extract in wheat crops under As toxicity has not been fully explored. The effectiveness of combining A. brasilense and seaweed extract in reducing As toxicity in wheat production was examined in this study through a 2-year pot experiment with nine treatments The treatments include a control with no additives and two As concentrations, 50 μM and 70 μM. At 50 μM and 70 μM, As is tested alone, with seaweed extract, with A. brasilense, and with both. Significant results were achieved in reducing the toxicity of As in wheat crop in the experiment. Arsenic at 70 μM was more harmful than at 50 μM. A. brasilense and seaweed extract applied together proven to be more effective, improving crop growth rates, chlorophyll levels, and stomatal conductance. The combined application was resulted in a notable decrease in the concentration of As in wheat plants. This was concluded that the application of A. brasilense and seaweed extract not only improve wheat growth but can also improve soil parameters under As toxicity conditions by increasing organic matter contents, boosting nutrients availability and increasing the production of antioxidant enzymes.